A Review of Bekasi City (West Java, Indonesia) Regional Archives and Library Office Service Transformation Policy Strategy - Moh Ilham A Hamudy; M Saidi Rifki (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2024)
Background: This study analyzes the Bekasi City Regional Archives and Library Office ‘s organizational management issues, specifically budget and human resources. The analysis applies Philip Kohler's organizational management theory